Chapter Peripheries - Forte , Giuseppina (Ricerche. Architettura, Pianificazione, Paesaggio, Design, 2022)
Peripheries are processes and places in which conditions and actors constantly shift. The contingent forms of peripheries in this book are assembled around embodied identities and are rooted in specific genealogies: peripheries as urban fringes, periphery countries in the modern world-system theory, and peripheral urbanization. Through these genealogies, the heterogeneous forms of peripheries acquire layered meanings that decenter urban theory. Since no form can exist outside historical relations of power, it is critical to apply methodological approaches that can address the political agency emerging from embodied identities.